2009
DOI: 10.1185/03007990903167415
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting score differences in the Insomnia Severity Index: using health-related outcomes to define the minimally important difference

Abstract: Based on results of the study, a 6-point reduction is recommended to represent a clinically meaningful improvement in individuals with primary insomnia. Research on generalizability of the recommended MID in this study to other patient populations and other type of treatment interventions is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(162 citation statements)
references
References 41 publications
4
158
0
Order By: Relevance
“…62 These findings merit future study given our previous cross-sectional work in which insomnia was associated with both self-reported and objective functional performance, including a 100-foot decrement in six-minute walk distance. 5 Consistent with previous work, 5 the HF patients were not overall excessively sleepy, a finding possibly related to high levels of sympathetic arousal associated with both insomnia and HF.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…62 These findings merit future study given our previous cross-sectional work in which insomnia was associated with both self-reported and objective functional performance, including a 100-foot decrement in six-minute walk distance. 5 Consistent with previous work, 5 the HF patients were not overall excessively sleepy, a finding possibly related to high levels of sympathetic arousal associated with both insomnia and HF.…”
Section: Discussionmentioning
confidence: 96%
“…The mean decrease of more than 7 points in insomnia severity in the CBT-I group, compared with a smaller decrease in the attention-control group exceeded the 6-point criterion indicative of clinical improvement and improved daytime function. 62 The mean ISI score at follow-up indicated that the typical patient experienced remission of insomnia. In the CBT-I group, 76% improved across one or more levels of insomnia severity and no one deteriorated, while 41% of the attention-control group improved, and 10% deteriorated.…”
Section: Resultsmentioning
confidence: 99%
“…Subjective sleep efficiency could not be calculated because time in bed was not captured on the patient diaries. In addition, we assessed: WASO by hour of night; the percentage of responders using various definitions (ISI ≥ 6 point improvement from baseline 22 ; sTSO and sTST ≥ 15% improvement from baseline, with the cutoff corresponding to the degree of change likely to exceed the mean placebo change from baseline based on historical data from similarly designed clinical trials conducted by Merck); and efficacy in subgroups defined by age, gender, race, region, baseline severity (above or below the median for the corresponding baseline values of the endpoint), cohort (Q or PQ), and, for the PQ-cohort only, by Q-cohort entry criteria (those who met Qcohort entry criteria versus those who did not).…”
Section: Efficacy Endpointsmentioning
confidence: 99%
“…41 The ISI is a 7-item self-report questionnaire, which has been validated for detecting the caseness of insomnia disorder, quantifying severity, and assessing treatment response. 39,40 Participants completed 2 separate versions of the ISI: one referencing the period when they were untreated, and the other targeting the period when they were on BzRAs for their insomnia. The latter began with the following prompt: "Please rate the severity of your insomnia symptoms while taking [endorsed BzRA]".…”
Section: Insomniamentioning
confidence: 99%
“…As an insomnia disorder diagnosis is symptom based, patient-reported outcomes offer the most valid metric for gauging treatment effectiveness and were hence the primary endpoints in this study. Treatment "response" was determined per empirically validated criteria for the MID in symptomatology, 39 and remission was operationalized as a reduction in symptoms to subclinical levels. 40 …”
Section: Introductionmentioning
confidence: 99%